2004
DOI: 10.1105/tpc.104.024216
|View full text |Cite
|
Sign up to set email alerts
|

The SPA Quartet: A Family of WD-Repeat Proteins with a Central Role in Suppression of Photomorphogenesis in Arabidopsis

Abstract: The Arabidopsis thaliana proteins suppressor of phytochrome A-105 1 (SPA1), SPA3, and SPA4 of the four-member SPA1 protein family have been shown to repress photomorphogenesis in light-grown seedlings. Here, we demonstrate that spa quadruple mutant seedlings with defects in SPA1, SPA2, SPA3, and SPA4 undergo strong constitutive photomorphogenesis in the dark. Consistent with this finding, adult spa quadruple mutants are extremely small and dwarfed. These extreme phenotypes are only observed when all SPA genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
327
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 207 publications
(346 citation statements)
references
References 40 publications
19
327
0
Order By: Relevance
“…The plates were kept at 4°C in the dark for 3 to 4 days to stratify and then exposed to 3 h of white light at room temperature before being placed in the dark for 21 h. The plates were incubated at 21°C for an additional 3 days in the dark or light as indicated. Arabidopsis thaliana wild type and various mutants (pif1, cop1-4, cop1-6, spa1, spa2, spa12, spa123, spa124, spaQ, cul1-6, cul3a, cul3b, cul3ab, cul4-1 and cul4cs) in the Col-0 background were used 6,32,[40][41][42][43][44][45][46][47][48] . For generation of different spaQpif1 mutant, pif1 and spaQ were crossed to obtain the F1 seeds.…”
Section: T a P -P I F 1 / C O P 1 -H A T A P -P I F 1 T A P -P I Fmentioning
confidence: 99%
“…The plates were kept at 4°C in the dark for 3 to 4 days to stratify and then exposed to 3 h of white light at room temperature before being placed in the dark for 21 h. The plates were incubated at 21°C for an additional 3 days in the dark or light as indicated. Arabidopsis thaliana wild type and various mutants (pif1, cop1-4, cop1-6, spa1, spa2, spa12, spa123, spa124, spaQ, cul1-6, cul3a, cul3b, cul3ab, cul4-1 and cul4cs) in the Col-0 background were used 6,32,[40][41][42][43][44][45][46][47][48] . For generation of different spaQpif1 mutant, pif1 and spaQ were crossed to obtain the F1 seeds.…”
Section: T a P -P I F 1 / C O P 1 -H A T A P -P I F 1 T A P -P I Fmentioning
confidence: 99%
“…Previous studies demonstrated that the transcript levels of SPA1, SPA3, and SPA4 are upregulated by various light signals, but the mRNA level of SPA2 is not altered in response to light (Hoecker et al, 1999;Laubinger et al, 2004;Fittinghoff et al, 2006). Here, we examined the protein expression patterns of these SPA genes under different light conditions.…”
Section: The Four Spa Proteins Exhibit Distinct Accumulation Patternsmentioning
confidence: 99%
“…Mutation in each individual SPA protein causes a weak or no phenotype defect, while the quadruple spa mutant displays a constitutive photomorphogenic phenotype similar to that of a strong cop1 mutant allele (cop1-5). Systematic phenotypic analysis of various combinations of spa mutants indicated that the four SPA genes confer partially redundant but not completely overlapping functions in mediating light responses at both seedling and adult stages (Laubinger and Hoecker, 2003;Hoecker et al, 2004;Laubinger et al, 2004Laubinger et al, , 2006Ishikawa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of wild-type (Col-0) Arabidopsis thaliana and various mutants (pif1, pif3, pif4, pif13, pif34, pif45, pif134, pif135, pif145, pif345, pifq, cop1-4, cop1-6, spa123, and hy5-215) in the Col-0 background were used (McNellis et al, 1994;Oyama et al, 1997;Laubinger et al, 2004;Leivar et al, 2008b). For the generation of different cop1, spa123, pif, and hy5-215 mutant combinations, cop1 and spa123 were first crossed with pif1, pif3, and pif4 to generate cop1-4 pif1, cop1-6 pif1, cop1-6 pif3, cop1-6 pif4, and spa123 pif1.…”
Section: Methods Plant Materials Growth Conditions and Measurementsmentioning
confidence: 99%
“…Among these COP/DET/FUS proteins, COP1 is a RING-type E3 ligase that is evolutionarily conserved from plants to vertebrates (Deng et al, 1992;Osterlund et al, 2000;Bianchi et al, 2003;Dornan et al, 2004;Yi and Deng, 2005;Lau and Deng, 2012). COP1 plays a central role in repressing photomorphogenesis in the dark by forming multiple complexes with SUPPRESSOR OF PHYTOCHROME A-105 (SPA1-4) family members in a tissue-and developmental stage-specific manner (Deng et al, 1992;Hoecker et al, 1999;Osterlund et al, 2000;Laubinger et al, 2004;Zhu et al, 2008;Lau and Deng, 2012). These complexes ubiquitylate and degrade positively acting transcription factors such as LONG HYPOCOTYL5 (HY5)/ LONG AFTER FAR-RED LIGHT1 (LAF1)/LONG HYPOCOTYL IN FAR-RED1 (HFR1) to repress photomorphogenesis in the dark (Hoecker et al, 1999;Saijo et al, 2003;Seo et al, 2003;Jang et al, 2005;Yang et al, 2005;Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%